Ecological Policy Implementation: Thematic Village Program to Address Slum Area Issues in Malang City - Walinegoro, Bhakti Gusti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Population density in Malang City causes various problems, one of which is slum areas. To overcome these problems, the Malang City Government issued a Thematic Village Program policy. This study aims to analyze the implementation of the Thematic Village Program through an ecological policy implementation model. The method used is qualitative through literature study. This study shows that ecological factors are indeed the main reason for the policy. The Thematic Village Program in Malang City is one of the programs that is in accordance with the concept of ecological policy, where the program aims to increase development, economy, and welfare, while still preserving the environment/overcoming environmental problems faced. In the context of implementation, the interaction of collaborating actors plays their respective roles in supporting the realization of policy objectives. The conclusion in this study is that although the formation of thematic villages has succeeded in reducing urban slum areas, other obstacles/challenges faced are related to the sustainability of the Thematic Village development. Therefore, the government and collaborating actors can initiate follow-up programs to maintain the sustainability of the Thematic Village Program.